Volatility Spillovers Among Selected Tourism Stock Indices - El Rifai, Oubayda (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
Volatility spillover is one of the most researched subjects in the finance literature due to its association with the transfer of risk between stock markets and portfolio management. The tourism sector has attracted significant attention from investors and scholars during the last two decades. Thus, the first concern of this thesis is to understand whether the volatility is transmitted among the major global tourism stock markets. Second, for portfolio diversification purposes, determine whether the effect of volatility transmission among tourism stock markets is temporary or persistent (long-lasting). For these purposes, Diebold and Yilmaz (2012) and Barunik and Krehlik (2018) time- and frequency-domain methods are adopted. Results suggest that total spillovers of the tourism stock indices rose significantly during the pandemic. Turkey and Italy are net volatility spillover transmitters, and others are net volatility spillover receivers. The results also indicate that the effect of volatility transmission among tourism stock markets is temporary (short-lasting). The findings suggest that short-term investors and portfolio managers should avoid investing in the tourism indices in the short term.

ÖZ: Hisse senedi piyasaları ve portföy yönetimi arasındaki risk transferi ile ilişkisi nedeniyle oynaklık yayılımı finans literatüründe en çok araştırılan konulardan biridir. Turizm sektörü son yirmi yılda yatırımcıların ve akademisyenlerin önemli miktarda ilgisini çekmiştir. Bu nedenle, bu tezin birincil amacı volatilitenin başlıca küresel turizm borsaları arasında yayılımını incelemektir. İkincisi, portföy çeşitlendirme amaçları için, turizm hisse senedi piyasaları arasındaki oynaklık yayılımı etkisinin geçici mi yoksa kalıcı mı (uzun süreli) olduğunu belirlemektir. Bu amaçla, Diebold ve Yılmaz (2012) ile Barunik ve Krehlik (2018) zaman ve frekans alanı yöntemleri benimsenmiştir. Sonuçlar, turizm hisse senedi endekslerinin toplam yayılmalarının pandemi sırasında önemli ölçüde arttığını göstermektedir. Türkiye ve İtalya net oynaklık yayılım vericileri ve diğerleri net oynaklık yayılım alıcılarıdır. Çalışmanın bulguları ayrıca turizm borsaları arasındaki oynaklık aktarımının etkisinin geçici (kısa süreli) olduğunu göstermektedir. Sonuçlar, kısa vadeli yatırımcıların ve portföy yöneticilerinin kısa vadede turizm endekslerine yatırım yapmaktan kaçınmaları gerektiğini göstermektedir.
Doctor of Philosophy in Finance. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2023. Co-Supervisor: Asst. Prof. Dr. Nigar Taşpınar and Supervisor: Prof. Dr. Nesrin Özataç.
Keywords: Thesis Tez; Banking and Finance Department; Stock exchanges; Capital movements--volatility Spillovers; Volatility Spillovers; Stock Market; Covid-19